2009
DOI: 10.1093/pubmed/fdp038
|View full text |Cite
|
Sign up to set email alerts
|

Does child gender determine household decision for health care in rural Thatta, Pakistan?

Abstract: Differential care seeking for boys and girls is not seen in Thatta despite clear differences in mortality ratios. This calls for more creative research to identify pathways for gender differential in child mortality. Factors identified as influencing child health care and amenable to modification include poverty alleviation and girls' education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
6
12
1
1
Order By: Relevance
“…Bypassing public PHC services for common childhood illness was more for boys than girls and this could be attributed to the society pediatrics' gender bias, explained by existence of strong sonpreference in Sudan, in line with studies of gender bias and health seeking actions in other African courtiers including Egypt, Tunisia, Morocco, and Nigeria [21][22][23]. Same findings are evident also from several studies from Asia including Nepal, Pakistan and China and Republic of Korea [24][25][26]. All the studies suggested that gender role affects the entire steps of child health care seeking action.…”
Section: Discussionsupporting
confidence: 61%
“…Bypassing public PHC services for common childhood illness was more for boys than girls and this could be attributed to the society pediatrics' gender bias, explained by existence of strong sonpreference in Sudan, in line with studies of gender bias and health seeking actions in other African courtiers including Egypt, Tunisia, Morocco, and Nigeria [21][22][23]. Same findings are evident also from several studies from Asia including Nepal, Pakistan and China and Republic of Korea [24][25][26]. All the studies suggested that gender role affects the entire steps of child health care seeking action.…”
Section: Discussionsupporting
confidence: 61%
“…For diarrhea, female children were less likely to get treatment from public HCP but the effect of gender bias was marginal. Gender bias against female child has been reported from some LMICs [21], [24], [36], [37], [40], [41]. However, there was no such bias for treatment of fever/cough in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, our analyses showed that children are likely to be treated outside, if they had severe symptoms (blood in stools, difficult or rapid breathing, and blocked chest/nose). Studies from LMICs have reported that children are likely to be taken for medical treatment if mother perceived the illness as serious [19], [21], [25], [35], [37][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size required used the following parameters: 80% power for detecting an estimated true effect of a magnitude of odds ratio 2.5, based on the probability of appropriate care (Po) of 30% in general population [13][14][15]. We estimated that 77 cases and two matched controls for each case (154 controls) were needed to fulfill the assumptions.…”
Section: Methodsmentioning
confidence: 99%